Slavery and essentialism in highland Madagascar - Regnier, Denis, author.
1 online resource (194 pages)
Keywords: "This book explores the prejudice against slave descendants in highland Madagascar and its persistence more than a century after the official abolition of slavery. 'Unclean people' is a widespread expression in the southern highlands of Madagascar, and refers to people of alleged slave descent who are discriminated against on a daily basis and in a variety of ways. Denis Regnier shows that prejudice is rooted in a strong case of psychological essentialism: free descendants think that 'slaves' have a 'dirty' essence that is impossible to cleanse. Regnier's field experiments question the widely accepted idea that the social stigma against slavery is a legacy of pre-colonial society. He argues to the contrary that the essential construal of 'slaves' is the outcome of the historical process triggered by the colonial abolition of slavery: whereas in pre-abolition times slaves could be cleansed through ritual means, the abolition of slavery meant that slaves were transformed only superficially into free persons, while their inner essence remained unchanged and became progressively constructed as 'forever unchangeable'. Based on detailed fieldwork, this volume will be of interest to scholars of anthropology, African studies, development studies, cultural psychology, and those looking at the legacy of slavery"--